1990
DOI: 10.1111/j.1365-2125.1990.tb03773.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐dose pharmacokinetics and in vitro antimalarial activity of dapsone plus pyrimethamine (Maloprim) in man.

Abstract: 1 The multiple-dose kinetics of dapsone (DDS), its major metabolite monoacetyldapsone (MADDS) and pyrimethamine (PYR) were studied in six healthy adult male volunteers following weekly administration of Maloprim® (100 mg DDS plus 12.5 mg PYR). 2 After the last maintenance dose of Maloprim, the following kinetic parameters (mean values) were determined for DDS and PYR, respectively: maximum plasma concentration (Cmax) = 1,134 and 116 ng ml-1; elimination half-life (t½/2) = 23 and 105 h; plasma clearance (CL) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
5
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
6
5
0
1
Order By: Relevance
“…No K a or V d values in children have been published previously for either PYR or SDX. For the two drugs, the t 1/2 were in the same general range as those published previously for children (14,17,48) and for adults (1,2,5,6,13,15,17,21,22,23,29,33,44,45), and our results showed wide interindividual variability of both drugs in children. In a review, Butler et al (7) indicated that the V d for many drugs was greater in children than in adults and that elimination may be altered in children compared with adults.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…No K a or V d values in children have been published previously for either PYR or SDX. For the two drugs, the t 1/2 were in the same general range as those published previously for children (14,17,48) and for adults (1,2,5,6,13,15,17,21,22,23,29,33,44,45), and our results showed wide interindividual variability of both drugs in children. In a review, Butler et al (7) indicated that the V d for many drugs was greater in children than in adults and that elimination may be altered in children compared with adults.…”
Section: Discussionsupporting
confidence: 75%
“…In a review, Butler et al (7) indicated that the V d for many drugs was greater in children than in adults and that elimination may be altered in children compared with adults. This was the case for PYR, for which published mean V d values in adults ranged from 2.12 to 3.06 liters/kg (1,13,15,44), compared with 4.38 Ϯ 2.68 liters/kg in the children in our study; it was also true for SDX, for which published mean V d values in adults ranged from 0.13 to 0.15 liters/kg (13, 44) versus 0.39 Ϯ 0.33 liter/kg in children. No data comparing the PK behavior of sulfonamides in the absorption phase according to age (from newborn to adult) were found.…”
Section: Discussionmentioning
confidence: 99%
“…The mean elimination half-life of pyrimethamine was approximately 140 h, and this figure is in broad agreement with estimates made after oral dosing, which have ranged from 35 to 175 h (1,5,6,13). The present estimates for AUC 0-ϱ (and derived parameters, such as clearance and volume of distribution) vary markedly from those after oral dosing.…”
supporting
confidence: 76%
“…As expected on the basis of the half-lives of 23-25 hours for dapsone and 80-105 hours for pyrimethamine [28,29], serum concentrations of dapsone decreased considerably throughout the weekly dosing interval, whereas pyrimethamine levels remained relatively stable in most of the sera examined [20]. Maintenance of high serum levels may be less important for prophylaxis than for cure, as shown by the experience with weekly doses of dapsone [18] and that with intermittent doses of trimethoprim-sulfamethoxazole [6,24,30]: both regimens prevented PCP, although the dosing interval exceeded the half-life of the individual compounds severalfold.…”
Section: Discussionmentioning
confidence: 64%